The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10554-011-9956-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the ascending aorta diameter in patients with severe bicuspid and tricuspid aortic valve stenosis using dual-source computed tomography coronary angiography

Abstract: We aimed to evaluate the diagnostic performance of dual-source computed tomography coronary angiography (DSCT-CA) in the measurement of the ascending aorta (AA) diameter and compare the AA diameter in patients with severe bicuspid aortic valve (BAV) and tricuspid aortic valve (TAV) stenosis. Eighty-eight consecutive patients (50 men, mean age 60.3 ± 13 year) with severe aortic stenosis (AS) underwent DSCT-CA before aortic valve surgery. Seventy-four of the 88 patients underwent cardiovascular magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The sensitivity and specificity of angioscans have increased greatly in the last few years reaching up to 100% [20], thus becoming comparable to MRI. Recently, a published study [21] demonstrated that dual source CT scan is as accurate as MRI in documenting TAA diameters in patients with BAV and a stenotic aortic valve which comes to reinforce the role of CT scanning in the diagnosis of TAA dilatation.…”
Section: Diagnosismentioning
confidence: 96%
“…The sensitivity and specificity of angioscans have increased greatly in the last few years reaching up to 100% [20], thus becoming comparable to MRI. Recently, a published study [21] demonstrated that dual source CT scan is as accurate as MRI in documenting TAA diameters in patients with BAV and a stenotic aortic valve which comes to reinforce the role of CT scanning in the diagnosis of TAA dilatation.…”
Section: Diagnosismentioning
confidence: 96%
“…Little is known how the modified anatomy of BAV patients affects the definition of the annulus plane [21,22]. As a consequence, the abovementioned technique based on the three hinge points has been previously applied also to datasets of patients with BAV regardless of valve type [13,[28][29][30]. We did not find this method feasible for all BAV patients.…”
Section: Discussionmentioning
confidence: 94%
“…Adhesion or fusion at the valve junction may lead to restriction of valve opening and valve orifice stenosis, consequently resulting in a series of morphological changes in the right ventricle and pulmonary artery. In addition, abnormalities in the number of pulmonary artery valve or dysplasia trigger PS ( 21 ). Congenital heart disease is often associated with bicuspid valve malformation, valves and valve annulus dysplasia, as well as fusion at the valve junction ( 22 ).…”
Section: Discussionmentioning
confidence: 99%